Philosophical Interactions with Parapsychology - Price, H. author. aut Link
XIX, 294 p.
Keywords: This is a collection of the most important writings of Oxford philosopher H.H. Price on the topics of psychical research and survival of death, collected from a wide variety of sources unavailable to most interested readers. Included are discussions of telepathy, clairvoyance, telekinesis, precognition, hauntings and apparitions, the impact of psychical research on western philosophy and science, and what afterlife is probably like. Few twentieth century English-speaking philosophers have written much on these topics. Of those who did so and whose writings have not been collected and published in a single source, H.H. Price was the most important.